Pengaruh Capital Intensity Ratio dan Profitability Terhadap Tax Avoidance (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode 2016-2018) - Armani, Dhea Nurul; Yulia Syafitri; Nova Begawati (Fakultas Ekonomi, Universitas Ekasakti, 2023)
This study aims to determine whether the Capital Intensity Ratio and Profitability proxy with ROA have a significant effect on Tax Avoidance in Manufacturing Companies Listed on the Indonesia Stock Exchange for the 2016-2018 period, either partially or simultaneously. The type of data used in this study is quantitative data sourced from the company's financial statements. Sources of data in this study is secondary data. The population in this study are manufacturing companies listed on the Indonesia Stock Exchange totaling 160 companies. The sampling technique used purposive sampling technique according to predetermined criteria. Based on predetermined criteria, a sample of 36 companies was obtained. The analytical method used in this study is multiple linear regression analysis and hypothesis testing using t test and f test. The results of this study indicate that partially Capital Intensity Ratio has no significant effect on Tax Avoidance and Profitability has a significant effect on Tax Avoidance. While simultaneously Capital Intensity Ratio and Profitability have a significant effect on Tax Avoidance.